Correcting the Eyesight: Cosmopolitanism in Chinua Achebe’s Things Fall Apart - AYDIN, Asım (Journal of History Culture and Art Research, 2015)
Correcting the Eyesight: Cosmopolitanism in Chinua Achebe’s Things Fall Apart Abstract The evolutionary process of separatist efforts such as colonialism, imperialism, globalization, neo-colonialism or any nationalism are outdated because global resources are becoming scarce every day, so such terms as human solidarity, Cosmopolitanism, and co-existence will have to endure in order to make use of the resources in the most optimum way. Mankind will have to understand that global sameness has to prevail despite long years of hostility, violence and bloodshed. In line with such an understanding, cosmopolitanism, as a term refers to world citizenship and 'a tolerance for things and people who are different’ and 'morality which is not rooted locally, but globally.’ Chinua Achebe tries to change the African images created by the writers depending on Eurocentric and Afrocentric perspectives. He handles the same periphery from an unusual viewpoint that is because he utilizes a different approach in representing Africa and composes counter discourses in response to colonial, imperial and racial discourses presented in colonial contexts.